2009
DOI: 10.1016/j.bbr.2008.08.048
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic α7- or β2-containing receptor knockout: Effects on radial-arm maze learning and long-term nicotine consumption in mice

Abstract: Classically, it has been thought that high-affinity nicotinic receptors containing β2 subunits are the most important receptor subtypes for nicotinic involvement in cognitive function and nicotine selfadministration, while low affinity α7-containing nicotinic receptors have not been thought to be important. In the current study, we found that knockout of either β2 or α7 subunits caused significant deficits in spatial discrimination in mice. The character of the impairment in the two knockouts was different. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(101 citation statements)
references
References 31 publications
(39 reference statements)
3
97
0
1
Order By: Relevance
“…Conversely, working memory improved after administration of nicotinic agonists (Chan et al 2007;Gatto et al 2004;Levin et al 1999;Lippiello et al 1996;Tatsumi et al 2006). A study with knockout mice substantiates these results further: both β2* and α7 knockouts have been connected to radial arm maze performance (Levin et al 2009). In a recent study, Rushforth et al (2010) have underlined the involvement of both the α4β2* and the α7 subtype in rats' working memory using not a maze task, but an odour span task.…”
Section: Working Memory-studies In Animalsmentioning
confidence: 76%
“…Conversely, working memory improved after administration of nicotinic agonists (Chan et al 2007;Gatto et al 2004;Levin et al 1999;Lippiello et al 1996;Tatsumi et al 2006). A study with knockout mice substantiates these results further: both β2* and α7 knockouts have been connected to radial arm maze performance (Levin et al 2009). In a recent study, Rushforth et al (2010) have underlined the involvement of both the α4β2* and the α7 subtype in rats' working memory using not a maze task, but an odour span task.…”
Section: Working Memory-studies In Animalsmentioning
confidence: 76%
“…Nicotine's reinforcing properties have been examined using a variety of behavioral, pharmacological antagonism, and genetic knockout approaches aimed at elucidating the nAChR subtype involved in nicotine reward (Picciotto et al, 1998). These studies generally indicate a greater importance of the ␣4␤2 subtype in mediating the reinforcing properties of nicotine, although it has been suggested ␣7 nAChRs may have a regulatory role for long-term maintenance of nicotine consumption (Levin et al, 2009). However, in a battery of studies comparing ABT-107 with nicotine we found no evidence of nicotine-like abuse liability.…”
mentioning
confidence: 99%
“…Furthermore, nicotine intravenous self-administration [Picciotto et al, 1998] and drug discrimination [Shoaib et al, 2002] were attenuated in b2-knockout mice. In contrast, drug discrimination was normal in a7 knockouts [Stolerman et al, 2004], but this receptor might be important for the long-term regulation of oral consumption of nicotine solutions [Levin et al, 2009]. Moreover, varenicline reduced the expression of nicotine sensitization in nicotine-sensitized rats [Zaniewska et al, 2008], putting the nicotinic receptor subtypes as relevant aims for further genetic studies.…”
Section: Introductionmentioning
confidence: 92%